Effect of rumen-protected fat on performance, carcass characteristics and beef qualityof the progeny from Nellore cows fed by different planes of nutrition duringgestation - Zamudio, Germán Darío Ramírez (2021)
Maternal nutrition can improve the development of fetal muscle and adipose tissues, which has an influence on the performance, carcass and meat traits of the offspring. In addition, the use of rumen-protected fat in finishing diets for the offspring from dams with adequate nutrition during pregnancy can be a donor source of fatty acids to increase the deposition of intramuscular fat in meat. Therefore, this study aimed to evaluate the effects of protein supplementation of Nellore cows grazing during the second and third trimester of gestation on the performance, carcass characteristics, meat quality and the expression of myogenic and lipogenic genes of offspring finished in feedlot on diets with or without inclusion of rumen-protected fat. Forty-eight immunocastrated Nellore steers with 341 ± 7.54 kg of initial body weight were distributed in a completely randomized design using a 2 × 2 factorial arrangement with the following treatments: two nutritional management conditions of the dams and two finishing diets of the progeny. After 124 ± 21 days of gestation until calving, half of the grazed cows received 1 kg/cow/day of protein supplement (SUPP; 36.9% of CP) and the other half only mineral salt (CTL). Steers born from dams of both groups were housed in individual pens (2 x 5 m) for 175 days, including 40 days of adaptation to the pens and diets. Half of each offspring was fed without (NFAT) or rumen-protected fat (RPF; 6% calcium salts), and both diets had 12.7% sugarcane bagasse and 87.3% concentrate. Initial and final body weight of steers and weight of feed and orts were recorded for measures of feedlot performance. Steers were slaughtered in a commercial slaughterhouse to assess the carcass traits and sampling of the longissimus thoracis muscle for gene expression analyzes. In addition, meat samples from longissimus lumborum were collected for qualitative analysis. In general, maternal supplementation did not affect feedlot performance, carcass characteristics and meat quality traits (P > 0.05). Maternal supplementation increased the expression of MyHC I and CPT2 (P < 0.05) and tended to up-regulate the FASN and ACACA genes (P < 0.10) in the offspring. Feeding with RPF decreased the dry matter intake, final body weight, average daily gain and carcass weight (P < 0.05), with no effect on feed efficiency (P = 0.60). Meanwhile, feeding with RPF increased the expression of MyHC I, MyHC IIx, IGFR1, COL3A1, FN1, ACACA (P < 0.05) and tended to up-regulate SREBF1 gene (P = 0.07). In conclusion, maternal supplementation and the use of the RPF in the finishing diet of offspring affected the expression of lipogenic genes in muscle, with no phenotypic effects on meat. Additionally, maternal nutritional management did not affect the performance or carcass characteristics of the offspring. In contrast, feeding RPF to steers affected feedlot weight gain and carcass weight, with no effect on feed efficiency.